Gypseous soil stabilization by alkaline activation method - Kadhim, Shaymaa Sadeq (2017)
Gypseous soils cover a large area in Iraq and other parts of the world. In general, these soils are problematic and very sensitive to the moisture content or any wet conditions. In fact, water is able to dissolve the gypsum/salt in the soil and consequently the soluble particles are leached out, causing huge changes in the volume and geotechnical properties of the soil mass. Although cement and lime can improve some engineering properties of gypseous soils, they have several shortcomings, especially when viewed from an environmental perspective (e.g. carbon dioxide emissions). Moreover, when gypseous soil is treated with the calcium-based materials (i.e. cement/lime), the stabilized soil has low durability due to the formation of ettringite, especially when the soil has a high amount of gypsum. Therefore, it is significant to investigate a proper method to stabilize gypseous soil. Alkali-activated binders were used as a new method of soil stabilization in this study. Due to the energy efficiency, the environmental friendly nature of the process, and the excellent resulting engineering properties, alkali-activated binders are fast emerging as materials of choice for soil stabilization. In this research, soil was collected from Babylon in Iraq. Different types of gypseous soils with different gypsum contents were prepared in order to identify the role of gypsum content in the soil. Fly ash class F was used as a precursor along with two types of activators at different molarities. Mechanical tests including compressive strength and mass loss and microstructural tests including XRD, BET, SEM, EDX, and TGA were performed on mortar before and after treatment and the effect of sulfate attack were investigated in the process. Gypseous soils were then treated with different alkaline activators for different curing times. Afterwards, UCS tests and collapsibility tests using the hydraulic Rowe cell system were performed to assess the effect of the treatment. Microstructural analyses were also performed to investigate the underlying mechanism. Finally, undrained triaxial tests were carried out to investigate the mechanical behaviour of the treated soils. This research also includes an attempt to find an empirical correlation to predict the collapse index based on soil properties using the results of collapsibility tests. The results showed that the alkaline activation method could stabilize the soils effectively. The collapse index decreased, and the mechanical performance of the treated soils improved. The microstructural analyses confirmed the durability of the stabilized mass. The study was important as it confirmed that the alkaline activation method played a dramatic role in the improvement of gypseous soil. In addition, series of Rowe cell and shear strength tests are performed on these three models of collapsible soils under various conditions. The results indicate that the most important parameters affecting soil collapsibility are; fine percent, initial dry unit weight, prewetting pressure and water content. Collapse potential decreases with the increase in initial dry unit weight and water content. It is found that only a relatively small fine percentage is required to yield significant collapse, and collapse potential increases with pressure at wetting and fine particles increase. Rate of increase in the collapse potential decreases as fine particles percentage increases. In un-soaked samples with 13% gypsum (G13), while for 25% gypsum content (G25), the collapse potential was 7.95 (moderately severe), and finally for the high gypsum content of 45% (G45), the collapse potential increased to 10.75 and was rated as severe. As can be seen that a large reduction in collapse potential was recorded with a high concentration of activator. For instance, the collapse potential of gypseous soil with 45% gypsum activated with 30% fly ash activated with 8-M KOH was 8.69%, but when the molarity of the activator was increased to 12 M under the same condition, the collapse potential decreased to 3.7% after 7 days of curing. On the other hand, the increase in the fly ash content from 10 to 30% reduced the collapse potential at different rates. As can be seen, the collapse potential for the soil with 45% gypsum content was 10.75 and decreased to 8.69, 5.88, and 3.7 in 12-M KOH samples and to 9.09, 6.64, and 4.48 in NaOH samples at 7 days when 10, 20, and 30% geopolymer fly ash was used to stabilize the gypseous soil. The result of UCS for the gypseous soil with 45% gypsum content treated with fly ash activated with 12-M KOH. It can be observed that the compressive strength of the untreated gypseous soil was 0.531 Mpa and it was increased after treatment with fly ash geopolymerized with 12-M KOH; the addition of 30% activated fly ash led to a significant enhancement, giving a compressive strength of 2.216 MPa with a strain 4.668 after 7 days of curing. Two collapse-predictive mathematical models are proposed by using the results of 165 Rowe cell tests. These models are of high and acceptable correlation factor of (r2=0.875and 0.87) and verified by experimental data.